2023
DOI: 10.1002/mus.27822
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of anti‐AChR‐MuSK‐LRP4 antibody‐negative myasthenia gravis in China

Abstract: Introduction/Aims: Descriptions of the clinical characteristics of anti-AChR-MuSK-LRP4 antibody-negative myasthenia gravis (triple-negative myasthenia gravis, TNMG) are lacking in the current literature. Therefore, we investigated the clinical characteristics of TNMG in Chinese patients.Methods: We retrospectively analyzed 925 patients with MG registered in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…Whether efgartigimod can improve the symptoms of triple-seronegative MG needs further study. Triple-seronegative MG has shown positive response to steroids and pyridostigmine, with approximately a third of patients achieving either complete stable remission or pharmacological remission (9). After 3-month treatment with pyridostigmine in combination with immunosuppressive therapy, the present patient achieved minimal symptom expression, which was defined as MG-ADL score of 0 or 1 and regarded as an practical tool for MG treatment goals (12).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Whether efgartigimod can improve the symptoms of triple-seronegative MG needs further study. Triple-seronegative MG has shown positive response to steroids and pyridostigmine, with approximately a third of patients achieving either complete stable remission or pharmacological remission (9). After 3-month treatment with pyridostigmine in combination with immunosuppressive therapy, the present patient achieved minimal symptom expression, which was defined as MG-ADL score of 0 or 1 and regarded as an practical tool for MG treatment goals (12).…”
Section: Discussionmentioning
confidence: 82%
“…The diagnosis and treatment are more challenging in tripleseronegative MG. As no detectable specific antibodies, diagnosis of triple-seronegative MG should be supported by adequate clinical characteristics and electrophysiological support, especially when the effectiveness of standard treatment is dissatisfactory. From a clinical point of view, it is observed that the clinical characteristics of triple-seronegative MG patients varied among different age groups (9). The overall prognosis of triple-seronegative MG is relatively good, with a low occurrence of crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Significant findings included a bimodal distribution of the age of onset (0–9 y/o and 40–49), coexisting thymic hyperplasia, and a generally favorable prognosis. Adult patients were more likely to have generalization from ocular forms, while juvenile subjects were more likely to experience clinical relapse [ 21 ].…”
Section: Epidemiological and Clinical Aspectsmentioning
confidence: 99%